VALUATION OF TEAR PRODUCTION DISORDERS IN COMPUTER VISUAL SYNDROME - Mamatkhujaev Minkhojiddin Sadirdinkhoji ugli; Mamatkhujaeva Gulnarakhan Najmidinovna (Innovate Conferences, 2025)
The modern digital environment has led to a sharp increase in the time people spend in front of computer screens, tablets, and smartphones. According to epidemiological studies, more than 70-80% of users who work at a computer for more than 3-4 hours a day experience signs of computer vision syndrome. One of the leading manifestations of computer vision syndrome is the disruption of tear fluid production and the dysfunction of the tear film, leading to a sensation of dryness, burning, redness of the eyes, and a decrease in visual comfort.Purpose of the study. The purpose of the study is to assess the state of tear production in computer users with signs of computer vision syndrome.